KONTRIBUSI TINGGI BADAN, BERAT BADAN, DAN PANJANG TUNGKAI TERHADAP KECEPATAN LARI CEPAT (SPRINT) 100 METER PUTRA (STUDI PADA MAHASISWA PENDKESREK ANGKATAN 2010 UNIVERSITAS NEGERI SURABAYA) - AJI PRADANA, AKHMAD Aji (Jurnal Kesehatan Olahraga, 2014)
KONTRIBUSI TINGGI BADAN, BERAT BADAN, DAN PANJANG TUNGKAI TERHADAP KECEPATAN LARI CEPAT (SPRINT) 100 METER PUTRA(Studi pada Mahasiswa IKOR Angkatan 2010 Universitas Negeri Surabaya)Akhmad Aji PradanaPendidikan Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, UNESAABSTRACTThe contributed factors of running speed includes physiological and anatomical factors. In other case, the previous research information about anatomical factor contribution to the running speed was still less. So this research was purposed to: 1) To determine the contribution of height to men sprint speed (sprint) 100 meters, 2) To determine the contribution of weight to men running speed (sprint) 100 meter, 3) To determine the contribution of the leg length to men running speed(sprint) 100 meters.Population of this research was men college of 2010 class on Pendkesrek major of UNESA. The total of sampel has been taken from population was 20 people and determined by Simple Random Sampling technique. The data analysis techniques using correlation analysis techniques and coefficients of determination with the help of SPSS software.The test results of data analysis showed: 1) The contribution of height to 100 meters sprint speed is equal to 62.57%. 2) The contribution of weight to the 100 meter sprint speed is equal to 1.93%. 3) The contribution of the leg length with the sprint speed of 100 meters is equal to 67.89%.Keywords: Contributions, height, weight, leg length, sprint